Weighted gene co-expression identification of CDKN1A as a hub inflammation gene following cardiopulmonary bypass in children with congenital heart disease - Chen, Huan; Liu, Jinglan; Wu, Yuqing; Jiang, Li; Tang, Mi; Wang, Xin; Fang, Xiaoling; Wang, Xi (Frontiers in Surgery, 2022)
Congenital heart disease (CHD) is the most common type of birth defect. Most congenital heart disease require surgery, and cardiopulmonary bypass (CPB) was employed for surgery. This study utilized weighted gene co-expression network analysis (WGCNA) to find key inflammation genes after cardiopulmonary bypass for congenital heart disease. We used the dataset GSE132176 for WGCNA analysis to find the module which was related to clinical traits. Then functional annotation and pathway enrichment analysis of genes in the module which related to clinical traits were performed by using the Metascape, an online analysis website. Finally, we identified hub genes by using two methods and verified through an independent dataset and western-bolttting. WGCNA analysis showed that the brown module had the highest correlation to cardiopulmonary bypass for congenital heart disease with 461 genes. Functional annotation and pathway enrichment analysis showed that genes in the brown module were enriched in inflammation-related GO and KEGG pathway. After the 30 most highly connected brown intra-module genes were screened, the protein-protein interactions(PPI) network was constructed by using STRING online analysis website. The PPI results were then calculated by using the 12 algorithms of the cytohubb plugin in cytoscape software. The final result showed that CDKN1A was the fundamental gene after cardiopulmonary bypass for congenital heart disease. In another independent validation dataset GSE12486, it was confirmed that CDKN1A was significantly differentially expressed between preoperatively and postoperatively in cardiopulmonary bypass (p<0.05). The results of Western-boltting also showed that the expression of CDKN1A protein was significantly higher CPB-after than CPB-before. Moreover, CDKN1A is mainly related to inflammation. In summary, through WGCNA analysis, CDKN1A has been determined and verified as the hub inflammation gene in cardiopulmonary bypass for congenital heart disease. It could serve as biomarkers and therapeutic targets for accurate diagnosis and treatment of inflammation after cardiopulmonary bypass in the future.